Analisis Audit Siklus Persediaan dalam Meningkatkan Akurasi dan Keandalan Laporan Keuangan Entitas Bisnis - Fitrah Sakinah; Samihah Ulvah; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study analyzes the role of inventory cycle auditing in improving the accuracy and reliability of financial reporting within business entities. Inventory is a critical component that influences key financial figures, making audit procedures essential to ensure that recorded values align with actual conditions. Using a descriptive–qualitative method, this research evaluates internal control structures, audit procedures, and common findings related to inventory discrepancies. The analysis reveals that weaknesses such as inadequate segregation of duties, inconsistent documentation, and manual data entry significantly increase the risk of material misstatements. Audit procedures including physical verification, reconciliation, and document tracing play a central role in identifying these issues and providing corrective recommendations. Furthermore, recurring audit findings highlight the need for stronger internal monitoring and the adoption of more reliable recording systems. The results indicate that effective inventory auditing enhances data integrity, reduces fraud risks, and supports more credible financial reporting. Ultimately, inventory cycle auditing serves as a strategic tool that contributes to organizational accountability and strengthens the overall quality of financial information.